Teachers’ Recruitment Procedure in Nigeria: Challenges and Prospects - Abimbowo, Yusuff Olatunji; Issa, Hammed Okiki (Pedagogik: Jurnal Pendidikan, 2024)
Nigeria is equally befallen with numerous challenges in its public-school teacher recruitment drive that negatively infiltrate its education system. This paper discusses the challenges experienced in recruiting teachers in public schools in Nigeria. Some forms of obstacles presented are characterized by bureaucratic bottlenecks, flaws in transparency, lack of adequate funding, and nepotism among others. This paper attempts to explore the chances to improve the method of recruiting teachers through policy reforms, increased financing and merit-based choosing criteria. The challenges include bureaucratic bottlenecks, impunity, lack of transparency, inadequate funding, and nepotism. The reform process would promote responsiveness to policy in recruitment through the possibility of further funding and the use of merit selection, and there would be far-reaching change in the process of online recruitment. If these problems are solved, and opportunities gradually positioned in their rightful places, the teacher recruitment process in Nigeria will be better and as such, the quality of education in this country will progress. Based on this, it is advised that any obstacles in the current selection process be routinely reviewed and fixed.